(untitled) (Aporte Santiaguino, 2024)
The negative incidents generated by constructions in the natural environment have forced the construction sector to adopt new sustainable practices to address this problem, hence the need to look for biodesign alternatives for key materials to change conventional practices for more sustainable ones. In this sense, the relevance of this study lies in the primary objective of analyzing the cases of biodesign of materials for construction as a sustainability strategy; For this purpose, a qualitative and exploratory study was undertaken, in which a series of biodesign cases were examined through a documentary analysis in the international and national context. The results found evidenced a series of biodesigns from renewable sources that turned out to be viable and very effective for construction, by offering not only adequate physical and mechanical properties, but also crucial means to address pollution from the brick industry, mitigate damage to the environment, minimize waste generation and promote plastic recycling. In conclusion, the analysis of biodesigns for construction revealed important findings at the international and national level. At a global level, promising options were found with a broad focus on specific topics. At the national level, although there is a lack of research, significant advances were identified. It is recommended to focus on developing new sustainable materials and carry out long-term studies to evaluate their environmental impact.